The private sector in the Soviet Union and China - Armin Bohnet; Günter Jaehne (Intereconomics, 1989)
The private sector in the fields of agriculture, wholesaling and retailing, craft trades and light industry, already well-developed in the People's Republic of China and a number of Eastern European countries, is now to be given a more significant role in the Soviet Union. Moscow's economic reformers believe this will contribute to an improved standard of living, as has been the case in China during the economic reform which has now been underway since 1978/79. It is therefore tempting to compare the concepts underlying the reforms and the course they have taken in the two socialist “super-powers”, the key question being whether the Russians will achieve similar successes with their reforms, once all the teething troubles are overcome, to those of the Chinese.
Keywords: 330; Economic Systems